Method for lightweight tomato leaf disease recognition based on improved YOLOv11s - Chen, Dixin; Liu, Li; Zhao, Long; Shi, Yi; Wang, Fei; Meng, Dan; Zhao, Jianshe (International Journal of Agricultural and Biological Engineering, 2025)
Accurate detection of tomato leaf diseases is crucial for early prevention and ensuring agricultural production. This study addresses six tomato leaf diseases: bacterial spot, early blight, late blight, leaf mold, septoria leaf spot, and yellow leaf curl virus. A lightweight detection model, YOLO-LGS, is proposed to achieve efficient and automated disease detection. The dataset of tomato leaf diseases was first augmented to enrich the disease features, thereby improving the model’s detection performance. The YOLO-LGS model is built on the YOLOv11 architecture, incorporating lightweight group attention net (LWGANet) to reconstruct the backbone network, replacing the convolutional block with parallel spatial attention mechanism with the grouped channel-wise self-attention (GCSA) mechanism, and introducing separated and enhanced attention module (SEAM) into the detection head to balance performance and efficiency. Experimental results show that the YOLO-LGS model achieves an mAP50 of 0.693 and an F1 score of 0.677, outperforming other YOLO models (YOLOv8s, YOLOv9s, YOLOv10s, and YOLOv11s). Additionally, the model’s parameter size is only 6.333 M, and its GFLOPs is 13.4, representing reductions of 32.739% and 37.089%, respectively, compared to YOLOv11s, significantly lowering computational cost while maintaining detection performance. The results demonstrate the effectiveness of LWGANet, GCSA, and SEAM. The development of the YOLO-LGS model provides an efficient, lightweight solution for tomato leaf disease detection in resource-constrained environments. Keywords: YOLO, LWGANet, object detection, lightweight modelDOI: 10.25165/j.ijabe.20251805.9928Citation: Chen D X, Liu L, Zhao L, Shi Y, Wang F, Meng D, et al. Method for lightweight tomato leaf disease recognition based on improved YOLOv11s. Int J Agric & Biol Eng, 2025; 18(5): 298–305.